INTEGRASI NILAI EKONOMI ISLAM PADA PEMBERDAYAAN EKONOMI PEREMPUAN MELALUI SUSTAINABLE ENTREPRENEURSHIP DI SURABAYA - Yani, Fitri; Nindyaningtyas, Ullya (ITB AAS INDONESIA Surakarta, 2025)
This study aims to examine the integration of Islamic economic values into women’s economic empowerment through sustainable entrepreneurship in Surabaya. Employing a descriptive qualitative approach with five women entrepreneurs as key informants, the research explores how Islamic principles are applied in business practices and how these values contribute to sustainability and socio-economic improvement. The findings reveal that the entrepreneurs consistently implement core Islamic economic values, including the prohibition of riba, honesty, trustworthiness, and social responsibility through the practice of zakat, infaq, and sadaqah. A majority of the informants (80%) utilize interest-free financing, while 65% routinely allocate a portion of their business profits for zakat or infaq. Their entrepreneurial activities also reflect environmental, social, and economic sustainability, demonstrated by the use of environmentally friendly materials (70%) and the empowerment of local female labor (55%). These integrated practices have contributed to notable improvements in household income rising by 25–40% within the last two years—along with enhanced financial independence and managerial skills, with 75% of informants reporting increased confidence in making economic decisions for their families. The study further highlights the role of supporting factors such as participation in Islamic business communities (60%), entrepreneurship training, and access to digital marketplaces, with half of the informants already marketing their products online. Despite these advancements, challenges persist, including limited access to Islamic microfinance (40%), low digital literacy (35%), and intense market competition. Overall, the study concludes that integrating Islamic economic values into sustainable entrepreneurship provides a strategic pathway for strengthening women’s economic empowerment and promoting inclusive, sustainable development in Surabaya.